Challenges of the Colombian educational system for the implementation of the policy of prevention and eradication of child labor - Anzelin, Ingrid; Martinez, Jefferson Galeano; Parra Moreno, Ciro Hernando (Education Policy Analysis Archives, 2018)
Avoiding ruptures in educational trajectories due to social problems demands synergic actions between social policy and educational policy. This research gives an account of the elements that affect the articulation between these two policies, based on an instrumental case study that deepens the difficulties in the implementation process of the commitments assigned by the policy of prevention and eradication of child labor to the system educational. For the reconstruction of the case, policy documents of the last two decades were analyzed and 42 actors were consulted at different levels of the education and protection system in Colombia and Bogotá. It is found that the knowledge and interpretation of child labor, the articulation between the different levels of the educational system, and the technical and operational capacity of the actors that must implement the actions established by the policy of prevention and eradication of child labor inside the educational institutions, are indispensable factors to respond in a pertinent way to the reality of working students.